Metrology with a twist: probing and sensing with vortex light - Mingjian Cheng; Wenjie Jiang; Lixin Guo; Jiangting Li; Andrew Forbes (Light: Science & Applications, 2025)
Abstract Optical metrology is a well-established subject, dating back to early interferometry techniques utilizing light’s linear momentum through fringes. In recent years, significant interest has arisen in using vortex light with orbital angular momentum (OAM), where the phase twists around a singular vortex in space or time. This has expanded metrology’s boundaries to encompass highly sensitive chiral interactions between light and matter, three-dimensional motion detection via linear and rotational Doppler effects, and modal approaches surpassing the resolution limit for improved profiling and quantification. The intricate structure of vortex light, combined with the integration of artificial intelligence into optical metrology, unlocks new paradigms for expanding measurement frameworks through additional degrees of freedom, offering the potential for more efficient and accurate sensing and metrological advancements. This review aims to provide a comprehensive overview of recent advances and future trends in optical metrology with structured light, specifically focusing on how utilizing vortex beams has revolutionized metrology and remote sensing, transitioning from classical to quantum approaches.